2021
DOI: 10.1590/1984-0462/2021/39/2020305
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations of Children and Adolescents With Covid-19: Report of the First 115 Cases From Sabará Hospital Infantil

Abstract: Objective: To describe the clinical manifestations and severity of children and adolescents affected by COVID-19 treated at Sabará Hospital Infantil. Methods: This is a cross-sectional, retrospective, and observational study. All cases of COVID-19 confirmed by RT-qPCR of patients seen at the hospital (emergency room, first-aid room, and ICU) were analyzed. The severity of the cases was classified according to the Chinese Consensus. Results: Among the 115 children included, a predominance of boys (57%) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
10

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 12 publications
2
33
0
10
Order By: Relevance
“…Other studies have reported asthma prevalence rates among pediatric COVID-19 cases to vary from 0.5% (Wuhan, China) (22) to 20% (Washington, DC) (23) , and from 2% (Lombari and Luguria, Italy) (24) to 24% (New York City) (25) among admitted pediatric COVID-19 patients. This may be partly explained by variability in the local asthma prevalence, though at least one study in Brazil found a lower asthma prevalence rate among children with COVID-19 infection compared to the local general pediatric asthma prevalence (13% vs 20-25%), suggesting that there may be other contributors to the variability among studies (26) .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported asthma prevalence rates among pediatric COVID-19 cases to vary from 0.5% (Wuhan, China) (22) to 20% (Washington, DC) (23) , and from 2% (Lombari and Luguria, Italy) (24) to 24% (New York City) (25) among admitted pediatric COVID-19 patients. This may be partly explained by variability in the local asthma prevalence, though at least one study in Brazil found a lower asthma prevalence rate among children with COVID-19 infection compared to the local general pediatric asthma prevalence (13% vs 20-25%), suggesting that there may be other contributors to the variability among studies (26) .…”
Section: Discussionmentioning
confidence: 99%
“… [21] Data from larger paediatric cohorts recently confirmed such findings. [ 1 , 2 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] ] Diarrhoea is reported in two to 33% of patients, whereas nausea and/or vomiting is reported at a rate ranging from five to 35% ( table 1 ). The presence of abdominal pain - though not always reported - ranges from six to 35% ( table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Foram comparados os sintomas apresentados por pacientes de duas faixas etárias: faixa etária de até 3 anos e faixa etária de 3 a 18 anos. A presença de diarreia e vômitos foi encontrada com maior frequência entre os menores de 3 anos (comparativamente 24,1% vs. 1,8%, p= 0,001; 25,9% vs. 8,8%, p=0,02), ao passo que, o sintoma dor abdominal foi relatado com mais frequência entre os maiores (14% vs. 3,4%, p = 0,04) 8 .…”
Section: Pediatriaunclassified